Open versus closed intramedullary nailing of femur shaft fractures in adults: a systematic review and meta-analysis - Loay A. Salman (14150322) (2023)
Purpose This systematic review and meta-analysis aimed to compare the outcomes of open- versus closed-reduction and intramedullary nailing (IMN) of adult femur shaft fractures. Methods Four databases were searched from inception until July 2022 for original studies that compared the outcomes of IMN following open-reduction versus closed-reduction technique. The primary outcome was the union rate; the secondary outcomes were time to union, nonunion, malalignment, revision, and infection. This review was conducted in line with PRISMA guidelines. Results A total of 12 studies with 1299 (1346 IMN cases) patients were included, with a mean age of 32.3 ± 3.25. The average follow-up was 2.3 ± 1.45 years. There was a statistically significant difference in union rate (OR, 0.66; 95% CI, 0.45–0.97; p-value, 0.0352), nonunion (OR, 2.06; 95% CI, 1.23–3.44; p-value, 0.0056), and infection rate (OR, 1.94; 95% CI, 1.16–3.25; p-value, 0.0114) between the open-reduction and closed-reduction groups in favour of the latter. However, malalignment was significantly higher in the closed-reduction group (OR, 0.32; 95% CI, 0.16–0.64; p-value, 0.0012), whereas time to union and revision rates were similar (p = NS). Conclusion This study showed that closed-reduction and IMN had more favourable union rate, nonunion, and infection rates than the open-reduction group, yet malalignment was significantly less in the open-reduction group. Moreover, time to union and revision rates were comparable. However, these results must be interpreted in context due to confounding effects and the lack of high-quality studies. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00264-023-05740-x